DUKUNGAN KELUARGA TERHADAP PEMBERIAN VAKSIN COVID 19 PADA ANAK USIA SEKOLAH (6-11 TAHUN) - Eva Martini; Asep Suryadin; Dhinny Novryanthi; Sri Kurnia Dewi (Jurnal Ilmu Kesehatan MAKIA, 2022)
The Covid 19 virus began to enter Indonesia In 2020, this virus originated from China, namely Wuhan, which quickly spread throughout the world, including Indonesia. Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is the cause of the Covid 19 virus. WHO data on confirmed Covid 19 cases around the world exceeds 90 million. The provision of vaccinations is not only for adults or more than 11 years of age, but the government has set vaccinations for children of school age 6-11 years. Many parents prevent children from being given the vaccine. Parents who get in the way because they are influenced by bad issues (Hoaxes). Family support is important and key to accelerating the vaccination process. The purpose of this study was to determine the relationship between family support and the administration of the Covid 19 vaccine in school-age children (6-11 years). Types of quantitative research with Cross Sectional research design. The data collection technique used a gogle form questionnaire and analyzed using SPSS. Data analysis of Chi Squre Test. The sampling technique uses simple random sampling. The total sample was 43 respondents. The results of the study P Value value = 0.002 (P<0.05) Ho value was rejected and Ha was accepted. The conclusion is that there is a significant relationship between family support and the administration of the Covid 19 Vaccine in school-age children (6-11 years). The suggestion for the next study is the analysis of the factors that most influence family support for the administration of the Covid 19 Vaccine.